2020
DOI: 10.35495/ajab.2019.08.352
|View full text |Cite
|
Sign up to set email alerts
|

Plant Cis-regulatory elements: methods of identification and applications

Abstract: Biotic and abiotic factors badly affect the productivity and growth of plants and found the major yield-limiting factor in agriculture. In recent years, various cis-regulatory elements have been identified that can function as molecular switches to regulate the expression of stress-related genes. They comprise of insulators, silencers, promoters and enhancers. These elements mediate not only functional diversity, but also modulate plant physiology at all developmental stages. Thus, identifying and characterizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…Cis-regulatory elements are linear fragments of non-coding DNA. Cis-regulatory elements provide the binding sites for transcription factors [ 45 ]. They have many localizations, orientations, and activities in relation to genes.…”
Section: Resultsmentioning
confidence: 99%
“…Cis-regulatory elements are linear fragments of non-coding DNA. Cis-regulatory elements provide the binding sites for transcription factors [ 45 ]. They have many localizations, orientations, and activities in relation to genes.…”
Section: Resultsmentioning
confidence: 99%
“…In the promoter sequences, cis -elements were predicted to gain a better understanding of the role of DcSOD genes under different environmental conditions (Ijaz et al, 2020 ). Similar to tomato SlSOD genes, different stress, hormone, and light-responsive elements were identified, which were related to drought, anaerobic induction, and low temperature (Zhang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various previous researchers who used SSR markers for sunflower characterization at molecular data also found that sunflower lines had a clear tendency of grouping restorer and CMS lines into different clusters. For examining the genetic diversity in sunflower SSR, markers are a powerful as it reveals high level of polymorphism among sunflower lines (Lochner, 2011 ; Zia et al, 2014 ; Suresha et al, 2017 ; Ijaz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%